Textual Function on the Vocational High Student’s Textbook: A Systemic Functional Linguistics Approach - S, Aspriza; Sidabutar, Usman; Siahaan, Sahat Taruli (Lembaga Riset dan Inovasi Almatani, 2025)
This study aims to analyze the textual function in the Merdeka Belajar English textbook for 11th- grade vocational high school students using the Systemic Functional Linguistics (SFL) approach developed by M.A.K. Halliday. Employing a descriptive qualitative method and the interactive analysis model of Miles, Huberman, and Saldaña (2014), the study examines 37 sentences from exposition and image-based texts in Chapter 1 of the textbook. The analysis focuses on mood types and theme-rheme structures. The findings reveal that declarative mood is the most dominant (78.3%), highlighting the informative and explanatory nature of the texts. Interrogative (18.9%) are used rhetorically to engage readers, while one nominal fragment (2.7%) is also identified. All sentences (100%) contain a complete Theme–Rheme structure. Modal elements and finite verbal operators each appear in 16.2% of the data, indicating interpersonal interaction. Textual markers such as conjunctions (8.1%), conjunctive adjuncts (5.4%), and continuatives (2.7%) further support cohesion.This consistent use of thematic and mood structures supports coherence, facilitates reader comprehension, and enhances the effectiveness of the learning materials. The study provides insights for improving English textbook design tailored to vocational education needs. The analysis reveals that all three textual functions; Topical, Textual, and Interpersonal Themes are realized, with the Topical Theme being the most dominant. This highlights the text’s focus on clarity and structured information flow, while the minimal use of Interpersonal and Textual Themes reflects a formal, straightforward expository style.